2015
DOI: 10.1007/8904_2015_466
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Diffusion Tensor Imaging (DTI) Parameters with Decoppering Treatment in Wilson’s Disease

Abstract: Objective: This study was undertaken to analyse serially the effects of decoppering therapy on the clinical features, disability and MRI brain including DTI metrics in patients with Wilson's disease.Methods and Results: Thirty-five patients with clinically and serologically confirmed neuropsychiatric form of Wilson's disease (WD) on decoppering therapy were followed for a minimum duration of 1 year with serial assessment of their clinical features, disability status and serial MR imaging of the brain including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…DTI abnormalities including decreases in FA and increases in MD have previously been demonstrated in the white matter of newly diagnosed patients using region of interest analyses. 20 , 27 , 59–61 Associations between a neurological symptom score and increased MD in the anterior limb of the internal capsule and between a measure of disability and increased MD in frontal white matter have also been reported. 59 In one of the few previous prospective neuroimaging studies on Wilson’s disease, Lawrence et al .…”
Section: Discussionmentioning
confidence: 92%
“…DTI abnormalities including decreases in FA and increases in MD have previously been demonstrated in the white matter of newly diagnosed patients using region of interest analyses. 20 , 27 , 59–61 Associations between a neurological symptom score and increased MD in the anterior limb of the internal capsule and between a measure of disability and increased MD in frontal white matter have also been reported. 59 In one of the few previous prospective neuroimaging studies on Wilson’s disease, Lawrence et al .…”
Section: Discussionmentioning
confidence: 92%
“…Jadav et al used the technique of DTI to evaluate white matter abnormalities in WD, finding MD significantly increased in the bilateral internal capsules and midbrain, and FA significantly decreased in the frontal and occipital white matter, bilateral internal capsules, midbrain, and pons, while the images were normal appearing on conventional MRI [ 15 ]. Li et al showed lower FA and higher MD in bilateral thalamus in patients, and Lawrence et al found higher FA in white matter in the initial phase of the patients [ 14 , 23 ]. Besides, some other methods were applied to diagnosis and follow-up in WD, either.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the values of MD, AxD, and RD were increased to mm 2 /s instead of 10 −3 μm 2 /s. This approach has been performed previously …”
Section: Methodsmentioning
confidence: 99%